Role of bacterial ribosomes in barotolerance. - Pope, D H (1975)
The effects of high hydrostatic pressures on protein synthesis by whole cells and cell free preparations of Escherichia coli, Pseudomonas fluorescens, and Pseudomonas bathycetes were determined. Actively growing cells of P. bathycetes and P. fluorescens were less sensitive than were E. coli cells. Protein synthesis by cell free preparations of E. coli and P. fluorescens showed the same extent of inhibition as their respective whole cell preparations, whereas cell free preparations of P. bathycetes showed a marked increase in pressure sensitivity over whole cells. Protein synthesis by hybrid protein synthesizing cell free preparations (the ribosomes from one organism and the S-100 supernatant fraction from another) demonstrated that response to high pressure is dependent on the source of the ribosome employed. A hybrid system containing E. coli ribosomes and P. fluorescens S-100 shows the same sensitivity to pressure as a homologous E. coli system, whereas a hybrid containing P. fluorescens ribosomes and E. coli S-100 shows the greater pressure tolerance characteristic of the P. fluorescens homologous system.